1998
DOI: 10.1248/bpb.21.814
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Coptidis Rhizoma and Scutellariae Radix on Azoxymethane-Induced Aberrant Crypt Foci Formation in Rat Colon.

Abstract: This study was conducted to obtain effective cancer chemopreventive agents with low toxicity from medicinal herbs. The effect of aqueous extracts from 9 medicinal herbs with antiinflammatory effect were examined on the formation of azoxymethane (AOM)-induced aberrant crypt foci (ACF), putative preneoplastic lesions of the colon. Male F344 rats were treated with 15 mg/kg body weight of AOM once a week for two weeks. Herbal extract consisting of 2% of the diet was administered from 1 d prior to the first carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 0 publications
0
50
0
Order By: Relevance
“…Studies from our laboratory and others have shown that C. rhizoma, a berberine-rich herb obtained from the root of various Coptis plants, possesses antitumor and cancer-preventive properties. 9,12,18 Previously, we found that oral administration of C. rhizoma significantly prevented weight loss in nude mice bearing (n ϭ 9) (n ϭ 9) (n ϭ 9) (n ϭ 6) (n ϭ 6)…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Studies from our laboratory and others have shown that C. rhizoma, a berberine-rich herb obtained from the root of various Coptis plants, possesses antitumor and cancer-preventive properties. 9,12,18 Previously, we found that oral administration of C. rhizoma significantly prevented weight loss in nude mice bearing (n ϭ 9) (n ϭ 9) (n ϭ 9) (n ϭ 6) (n ϭ 6)…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, muscle wasting induced by PIF may be associated with elevation of prostaglandin E 2 (PGE 2 ), 23 and it is known that C. rhizoma inhibits cyclooxygenase-2 activity. 12 This herb might exert anticachectic action via direct interaction with PIF and PGE 2 -generating pathways. We also found that CR supplementation significantly prevented hypoglycemia in tumor-bearing mice compared to the normal diet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wnt/β-catenin has been shown to be one of the important targets for colon cancer chemoprevention. Berberine can inhibit carcinogen-induced formation of ACFs in the rat colon, which are usually considered to be preneoplastic lesions of colon mucosa (30). DMH-induced colon cancers are characterized by activating β-catenin mutations that are functionally equivalent to inactivating APC mutations (31,32).…”
Section: Discussionmentioning
confidence: 99%